Family Again! A pregnancy that brought hope - Akinsipe, Gbemisola.D (Spectrum Books Ltd, 2011)
Lonke, a girl just any young girl gets pregnant at 16. Her mum's confidence in her is betrayed, her dad becomes tired and her brothers are taken away. The pregnancy redefines the true meaning of family and a string of secrets, reasons questions, friendships and dreams are unraveled.
Keywords: family; Fiction; Teenage pregnancy